KEMAMPUAN PENERAPAN GCG DAN PENGUNGKAPAN CSR MEMODERASI PENGARUH KINERJA KEUANGAN PADA NILAI PERUSAHAAN - Damayanti, Ni Made Dwi; Wirawati, Ni Gusti Putu (E-Jurnal Akuntansi, 2014)
ABSTRACT The purpose of this study was to know the ability the implementation of GCG and CSR disclosure in moderating influence of financial performance on the firm value. Financial performance is proxied by ROE and firm value proxied by PBV. This study used a non financial company listed on the Stock Exchange and included in the ranking CGPI consecutive years 2010-2012. Samples were obtained by 10 non financial companies are determined using the purposive sampling technique. The analysis technique used is Moderated Regression Analysis (MRA). The results showed CSR disclosure able to moderate the influence of financial performance on firm value and the implementation of GCG was not able to moderate influence of the financial performance on firm value.
Keywords: financial performance, the firm value, the implementation of GCG and CSR disclosure